Having some difficulty making q the subject:
((a-c)/b(2+vj)-(q/2+vj) = ((a-c)/b)-q(2+vi)
Any help would be appreciated.
[(a-c)/(b(2+vj))]- q/2- [vj]= [(a- c)/b]- (2+vi)q
Get everything involving q on the left side, everything not involving q on the right side:
-q/2- (2+vi)q= (a-c)b+ vj- (a-c)/(b(2+vj))
Factor q out on the left:
(-1/2- 2+vi)q= (a-c)b+ vj- (a-c)/(b(2+vj))
Divide both sides by -1/2- 2+ vi:
q= [(a-c)b+ vj-(a-c)/(b(2+vj))]/(-1/2- 2+ vi)
Thank you for the reply, however, I still do not fully understand how you came to this conclusion. My notes tell me that a simpler version of this problem:
((a-c)/b)-q(2+v)=((a-c)/b(2+v))-(q/2+V) equates to q*= (a-c)/b(3+v) and I just don't understand how this is possible.